Student’s Experience of New Learning System in Covid-19 Pandemic - Firmansyah Firmansyah; Salmia Syarifuddin; Yetty Yetty; Susi Astiantih (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
The Covid-19 had changed the educational system in Indonesia. The students must be survived with the change of educational system. They are required to use the internet-based media and technology during covid-19 pandemic. This study aimed to explore how the students experience of the change of learning system from face to face learning to online learning and finding deep information from the students who life in the rural area. The present study applied qualitative research to explore how the students in Maluku Utara survive in distance learning by examine how their experience in online learning. The result of this study gives several contributions about the how the students experience in online learning in Maluku Utara. The first, in conducting online learning the students must struggle with the condition of network in Maluku Utara. There were some areas that is not supported by the network so the students must go to the area that has a good network. This phenomenon becomes the main problem of the students in having online learning. The second, the process of online learning conducted both synchronous and asynchronous. They use social media as the media of communication, giving information and instruction. The third, most of the students used smartphone as the device in conducting online learning. However, in some school the student who does not have smartphone used I-pad from their school. The last, the students from Maluku Utara were easy to adapt the new system of learning.